Determination of the relationship between the samples of instructional methods and techniques prepared for 4(th) and 5(th) grade primary school science and technology curriculum and the principles of situated learning in Turkey - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
Lauillard (1993) indicated the importance of association between object or fact and situation they included in the process of learning and teaching for educational quality. He supported that knowledge has an environmental nature and it can not be thought seperately from its environment. Besides this, he mentioned that students can not learn the concepts if they do not use. Lave (1996) specified that learning is influenced from the culture it arised, context and application. However at present, it was observed that knowledge presented in classrooms transferred to students abstracting its context and culture. This circumstance is caused usually students' failure solving problems in their real life. According to Young (1993), to prepare appropriate environment for situated learning, teachers should provide to students complex, real and problem-based activities to make their students achieve knowledge. In the process of situated learning, teachers should direct their students until they recognize this process and also they should provide their students necessary advanced information. In recent years, it is true that major changes are experienced in paradigim based on learning/teaching. From point of this view, it important to know that if the approach of situated learning has an in consistency with the sample of instructional methods and techniques presented for the teachers in primary education curriculum which based on constructivist approach and prepared for 4 and 5 grade Science and Technolgy Curricula. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: Situated learnig; science and technolgy curriculum; instructional methods and techniques